Analisis Perbandingan Penggunaan Borepile Dan Spunpile Terhadap Biaya Dan Waktu Pada Pembangunan Flyover Di Proyek Pembangunan Jalan Tol Betung – Tempino – Jambi Seksi 4 - Ega Oktarian Gusty; Harmes .; Putri Nurul Kusuma Whardani (GLOBAL SCIENTS PUBLISHER, 2026)
Toll road infrastructure development plays a strategic role in enhancing regional connectivity and economic growth, including in the Proyek Pembangunan Jalan Tol Betung – Tempino – Jambi Seksi 4. During the construction of the flyover at STA 161+650, a foundation design change was implemented from bore pile to spun pile based on updated soil investigation results indicating medium to hard soil layers at a depth of 26 meters. This study aims to analyze the comparison of cost and construction time between bore pile and spun pile foundations to determine the more efficient and economical method. This research employs a quantitative approach using a case study method. Secondary data were obtained from the Detail Engineering Design (DED), shop drawing review, 2024 Unit Price Analysis (AHSP), 2024 Standard Unit Price (SSH) of Jambi Province, and project S-curve. The analysis includes work volume calculation, Budget Plan (RAB) preparation, and time analysis using equipment productivity and the Critical Path Method (CPM). The results show that the total cost of the bore pile foundation is IDR 8,324,502,821.16 with a duration of 50 days, while the spun pile foundation costs IDR 6,150,004,815.25 with a duration of 44 days. Therefore, the spun pile foundation is 35% more cost-efficient and 14% faster than the bore pile method. The foundation design modification has proven to improve project effectiveness without compromising structural safety and technical requirements.